Aesthetic and cultural value of Nglanggeran ancient volcano geoheritage: A cultural geomorphology perspective - Insani, A.A. (EDP Sciences, 2023)
Nglanggeran Ancient Volcano is a residual hill over from an ancient volcano. The Government of the Republic of Indonesia and the Government of the Special Region of Yogyakarta have designated the area as a Geoheritage, but the aesthetic and cultural aspects of the landscape have not been studied further and are still considered separately. In fact, a landscape is composed of abiotic, biotic, and cultural aspects, all of which interact with each other in the earth system. This study focuses on the aesthetic and cultural aspects of Nglanggeran Ancient Volcano in the perspective of cultural geomorphology. The method used is descriptive qualitative exploratory method. Cultural and aesthetic values are explored through literature studies and field surveys. The results of this study are the immaterial cultural values and aesthetic values of the Nglanggeran Ancient Volcano Geoheritage, such as Nglanggeran Legend, Kampung Pitu’s Folklore, the beauty of nglanggeran landscape, nglanggeran ecotourism, and nglanggeran as artistic inspiration. This study will strengthen the legal basis of Nglanggeran Ancient Volcano as a geoheritage and provide scientific awareness of the relationship between aesthetic and cultural aspects and landforms in a landscape framework. © 2023 EDP Sciences. All rights reserved.